Delivering ITSM for business maturity : a practical framework - Weed-Schertzer, Beverly (Emerald points., 2019)
IT Service Management (ITSM) is an imperative part of achieving business maturity. Excellence in ITSM has previously been thought of only in terms of quality, customer satisfaction, and reduced costs - or, in other words, casting ITSM as only for technical units and not as part of the larger picture of business maturity. In this exciting new take on ITSM, leading expert Beverly Weed-Schertzer positions ITSM at the heart of company strategy to build a layered operating model. Delivering ITSM for Business Maturity: A Practical Framework helps business leaders and corporate thinkers navigate their way to a successful and high performing ITSM model. Using an original combination of yoga science and service management principles, Weed-Schertzer offers business professionals a way of taking back control of their ITSM program, and helps with innovation for those starting a new one. For anyone in the information technologies profession, or for managers of IT professionals, this book is an unmissable guide to creating a strong, forward-thinking foundation for ITSM processes.